The Holocaust in the British imagination: the official mind and beyond, 1945 to the present. Issue 3 (3rd July 2017) - Kushner, Tony
ABSTRACT: This article traces how the Holocaust has been responded to at a political level in Britain from 1945 to the present. It includes key moments such as the liberation of the camps in 1945, the Eichmann Trial in 1961, compensation schemes from the mid-1960s, and more recent forms of pedagogic and memorialization issues since the 1990s, ending with the Prime Minister's Holocaust Commission (2014 onwards). While the focus is on the official sphere, attention is given throughout to wider cultural and social trends and contexts for the whole period. It emphasizes the contrasting meanings and politics associated with British confrontations with the Holocaust in the postwar era, using for the more recent period especially the 2016 UCL survey What Do Students Know and Understand about the Holocaust?